2020
DOI: 10.21203/rs.3.rs-42172/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Pandemic Readiness Status of West Africa

Abstract: Background From the onset of COVID-19 pandemic in late December 2019, countries have been stepping up their pandemic preparedness and response activities in accordance with WHO recommendations. Informed by the recent lessons learned from the West Africa Ebola Virus Disease outbreak, and subsequent investments made in public health emergency preparedness and response in the Economic Community of West African States (ECOWAS) region, the West Africa Health Organisation (WAHO) is providing regional leadership in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Several publications have attempted to provide answers at country, 3,4 sub-regional [5][6][7][8] and continental [9][10][11] levels. These studies have shown several differences in morbidity, mortality, and response to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications have attempted to provide answers at country, 3,4 sub-regional [5][6][7][8] and continental [9][10][11] levels. These studies have shown several differences in morbidity, mortality, and response to the pandemic.…”
Section: Introductionmentioning
confidence: 99%